Analysis of endometrial carcinoma in young women at a high-volume cancer center. (August 2017) - Biler, Alper; Solmaz, Ulas; Erkilinc, Selcuk; Gokcu, Mehmet; Bagci, Mustafa; Temel, Orhan; Karadeniz, Tugba; Sanci, Muzaffer
Abstract: Objective: To investigate the clinicopathological characteristics, treatment, survival, and prognosis of endometrial cancer in women aged ≤40 years. Methods: Women who underwent surgery for endometrial cancer at a single high-volume cancer center between January 1995 and December 2014 were retrospectively reviewed. Women aged >40, patients with missing data, and those who did not undergo surgical staging were excluded. Univariate and multivariate regression models were used to identify the risk factors for overall survival and progression-free survival. Results: A total of 40 patients with endometrial cancer were assessed. The median age at diagnosis was 38 (range, 21–40) years, and most of the uterine tumors found were early-stage (85%), low-grade (67.5%), and endometrioid carcinomas (97.5%). The median serum cancer antigen 125 level was 10.9 IU/mL (range, 3–1284 IU/mL). Optimal cytoreductive surgery was achieved in 35 patients (87.5%). All patients underwent total abdominal hysterectomy, and 97.5% of the patients underwent hysterectomy plus bilateral salpingo-oophorectomy. Among the total group of 40 patients, 21 (52.5%) underwent pelvic and para-aortic lymph node dissection, and 15 (37.5%) underwent only pelvic lymph node dissection. Multivariate analysis confirmed that a cancer antigen 125 level ≥35 was the only independent prognostic factor for both progression-free survival (hazard ratio, 22.997; 95% confidence interval, 1.783–296.536; p = 0.016) and overall survival (hazard ratio, 22.541; 95% confidence interval, 1.75–290.364; p = 0, 017). Conclusions: Our study demonstrated that a cancer antigen 125 level ≥ 35 is the only independent prognostic factor for both progression-free survival and overall survival in patients aged ≤40 years with endometrial cancer. Highlights: Endometrial cancer is uncommon in patients 40 years of age and younger. The prognosis for EC among younger patients tends to be more favorable than that for older patients. CA 125 level ≥35 is the most significant factor affecting survival in patients with aged ≤40 years with endometrial cancer.